Accommodation Infrastructure and Employee Behavior Influence Guest Satisfaction at Kyriad Hotel Bumiminang Padang - Sasgia Febby Yolla; Youmil Abrian (Pt. Threeple Herphi Educate, 2026)
Preliminary researcher observations at Kyriad Hotel Bumiminang Padang indicated concerns involving facility condition and frontline service interactions, making it important to assess how both operational dimensions relate to guest satisfaction. This study examines the effects of accommodation infrastructure and employee behavior on guest satisfaction. A quantitative causal-associative survey design was applied to a reported population of 1,673 hotel guests, with 323 respondents selected through non-probability purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed with descriptive statistics and multiple linear regression in SPSS 26. Accommodation infrastructure (mean = 40.99), employee behavior (mean = 27.83), and guest satisfaction (mean = 31.16) were all classified as good. Accommodation infrastructure had a positive and significant effect on guest satisfaction (B = 0.422, t = 11.224, p < 0.001), and employee behavior also had a positive and significant effect (B = 0.362, t = 6.941, p < 0.001). Together, both predictors were significant (F = 314.988, p < 0.001) and explained 66.1% of the variance in guest satisfaction (adjusted R² = 0.661). Accommodation infrastructure was the stronger predictor, indicating that facility maintenance should be prioritized while employee-service development is strengthened in parallel.